2018
DOI: 10.1007/s00209-018-2172-4
|View full text |Cite
|
Sign up to set email alerts
|

$$A_p$$ A p Weights and quantitative estimates in the Schrödinger setting

Abstract: Part of the intrinsic structure of singular integrals in the Bessel setting is captured by Muckenhoupt-type weights. Anderson-Kerman showed that the Bessel Riesz transform is bounded on weighted L p w if and only if w is in the class A p,λ . We introduce a new class of Muckenhoupt-type weights A p,λ in the Bessel setting, which is different from A p,λ but characterizes the weighted boundedness for the Hardy-Littlewood maximal operators. We also establish the weighted L p boundedness and compactness, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…We prove Theorem 1.3 in Section 2 by borrowing some ideas from [1], where Bongioanni et al introduced a ρ-localized method to obtain the boundedness of operators associated to the Schrödinger operator L on weighted Lebesgue spaces. This is quite different from the method used in [12]. Besides this, we also need a quantitative version of the extrapolation theorem for A ρ, θ p (R n ) weights (see Lemma 2.6 below).…”
Section: Remark 14mentioning
confidence: 99%
See 2 more Smart Citations
“…We prove Theorem 1.3 in Section 2 by borrowing some ideas from [1], where Bongioanni et al introduced a ρ-localized method to obtain the boundedness of operators associated to the Schrödinger operator L on weighted Lebesgue spaces. This is quite different from the method used in [12]. Besides this, we also need a quantitative version of the extrapolation theorem for A ρ, θ p (R n ) weights (see Lemma 2.6 below).…”
Section: Remark 14mentioning
confidence: 99%
“…Moreover, the weighted boundedness, related to A ρ, θ p (R n ), of many operators associated to the Schrödinger operator L := −∆ + V was obtained in [1,2,16,23,25,26]. Recently, Li et al [12] introduced the fractional weight class A ρ, θ p, q (R n ) adapted to L and obtained the quantitative weighted boundedness of the fractional maximal function and the fractional integral operator associated to L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the quantitative weighted bounds for operators in the Schrödinger settings have been investigated by many researchers. Li et al [18] established the quantitative weighted boundedness of maximal functions, maximal heat semigroups, and fractional integral operators related to L. In 2020, Zhang and Yang [19] showed that the quantitative weighted boundedness for Littlewood-Paley functions in the Schrödinger setting. Bui et al [20] investigated the quantitative boundedness for square functions with new class of weights.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the results in [18,19,22], in this paper, we investigate the quantitative weighted boundedness of Littlewood-Paley functions generated by fractional heat semigroups associated with L. Let K L t ð•, • Þ denote the integral kernel of the heat semigroup fe −tL g t≥0 . For α > 0, the subordinative formula (cf.…”
Section: Introductionmentioning
confidence: 99%